Donor Simvastatin Treatment in Heart Transplantation: A Randomized and Blinded Clinical Trial. Issue 8 (20th August 2019) - Nykänen, Antti I.; Holmström, Emil J.; Tuuminen, Raimo; Krebs, Rainer; Dhaygude, Kishor; Kankainen, Matti; Jokinen, Janne J.; Lommi, Jyri; Helanterä, Ilkka; Räisänen-Sokolowski, Anne; Syrjälä, Simo O.; Lemström, Karl B.
Abstract : Background: Ischemia-reperfusion injury may compromise the short-term and long-term prognosis after heart transplantation. Experimental studies show that simvastatin administered to the organ donor is vasculoprotective and inhibits cardiac allograft ischemia-reperfusion injury. Methods: Eighty-four multiorgan donors were randomly assigned to receive 80 mg of simvastatin (42 donors) via nasogastric tube after declaration of brain death and upon acceptance as a cardiac donor, or to receive no simvastatin (42 donors). The primary efficacy end point was postoperative plasma troponin T and I levels during the first 24 hours after heart transplantation. Secondary end points included postoperative hemodynamics, inflammation, allograft function, rejections and rejection treatments, and mortality. Results: Organ donor simvastatin treatment significantly reduced the heart recipient plasma levels of troponin T by 34% (14 900 ± 12 100 ng/L to 9800 ± 7900 ng/L, P =0.047), and troponin I by 40% (171 000 ± 151 000 ng/L to 103 000 ± 109 000 ng/L, P =0.023) at 6 hours after reperfusion, the levels of NT-proBNP (N-terminal pro-B-type natriuretic peptide) by 36% (32 800 ± 24 300 ng/L to 20 900 ± 15 900 ng/L; P =0.011) at 1 week, and the number of rejection treatments with hemodynamic compromise by 53% within the first 30 days ( P =0.046). Donor simvastatin treatment did not affect donor lipid levels but was associated with a specific transplant myocardial biopsy gene expression profile, and a decrease in recipient postoperative plasma levels of CXCL10 (C-X-C motif chemokine 10), interleukin-1α, placental growth factor, and platelet-derived growth factor-BB. Postoperative hemodynamics, biopsy-proven acute rejections, and mortality were similar. No adverse effects were seen in recipients receiving noncardiac solid organ transplants from simvastatin-treated donors. Conclusions: Donor simvastatin treatment reduces biomarkers of myocardial injury after heart transplantation, and—also considering its documented general safety profile—may be used as a novel, safe, and inexpensive adjunct therapy in multiorgan donation. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT01160978. Abstract : Supplemental Digital Content is available in the text.